Legislate, Educate, Integrate: Three Steps to Help Teenagers Coexist with the Internet - LaRose, Summer (Maine Policy Review, 2024)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2024 asked students to recommend guidelines that we should establish concerning teenagers’ use of technology to ensure their personal safety and privacy. Essays have been edited for length.